Application of design of experiment technique in the nickel-chromium electroplating process on WC-Co substrate prior hfcvd diamond coating - Ayoob Ahrari, 1982-; Noordin Mohd. Yusof, supervisor; Fakulti Kejuruteraan Mekanikal (2010)
Thesis (Sarjana Kejuruteraan (Mekanikal - Teknologi Pembuatan Termaju)) - Universiti Teknologi Malaysia, 2010